Pelatihan Pembuatan Pupuk Organik Cair dari Urin Kelinci pada Kelompok Peternak "Kelinci" di Desa Tanjungsari Kecamatan Panekan Kabupaten Magetan - Wuye Ria Andayanie (JURNAL DAYA-MAS, 2021)
Raising rabbits is one of the main activities of the business group in Tanjungsari Village, Panekan District, Magetan Regency. Raising rabbits provides several advantages, including: 1) feed that is easy to obtain and cheap; 2) easy maintenance method; 3) the number of children produced from the parent is counted. In addition, rabbit urine can be used for liquid organic fertilizer. Rabbit urine as one of the mainstay organic fertilizers for farmer groups in Panekan District, so far the potential of rabbit urine has not been developed optimally. The objectives of this activity are to: (1) utilize waste derived from rabbit urine; (2) improve the management of rabbit breeder groups. The method used is education and facilitation. Education is carried out by: (1) providing counseling to groups of rabbit breeders for the manufacture of organic fertilizer derived from rabbit urine; (2) introduction of fertilizer-making equipment; (3) assistance for training on the use of tools, group motivation, marketing management of organic fertilizer products derived from rabbit urine. Facilitate by providing appropriate tools needed by the group for the manufacture of organic fertilizers. This effort is carried out to utilize waste derived from rabbit urine and increase economic added value for rabbit breeders.